Formulation and evaluation of cream from stem barksof Pithecellobium Jiringa / Zurhana Mat Hussin and Nurin Adila Zakry Irfan Zakry - Mat Hussin, Zurhana; Irfan Zakry, Nurin Adila Zakry (Universiti Teknologi MARA Cawangan Pahang, 2020)
The demand of herbal cream has increased rapidly in the market due to the herbs' natural content which does not pose any side effects on the human skin. In the present study, we investigated the ethyl acetate extract of Pithecellobium jiringa (P. jiringa) stem barks as antibacterial cream. The antioxidant potential of the P. jiringa extract was evaluated by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Six formulations of antibacterial creams (oil in water) were prepared and labelled as F1 to F6. All formulations were characterized by different parameters such as pH, spread ability and stability. These formulations were then investigated for their antibacterial activity against several bacteria such as Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Klebsiella pneumonia (K. pneumonia) and Bacillus cereus (B. cereus) by using agar disc diffusion technique. The DPPH scavenging activity showed moderate radical scavenging activity with IC50 value was 46.25 µg/mL. Among the six formulations, F6 showed the good spread ability, homogeneity, appearance and pH. The formulation did not show any phase separation and was easy to remove. The F6 formulation also showed no irritations on skin such as redness, edema, or erythema in irritancy studies. In microbiological assay, F6 formulation exhibited the largest zone inhibition against Staphylococcus aureus which was 11.52 mm at the concentration of 2.0% w/v. Therefore, the study suggests that the F6 can be safely used for the consumers that have skin irritations caused by bacteria.